A Study of Occupy D.C.: The Global Psychology Perspective - Pradhan, Deepti; Trullinger, Mark; Thatcher, Joyce; Morales, Gerson; Riggins, Nickesha; Beck, Stephanie; Carroll, Shirley (European Scientific Journal, ESJ, 2016)
The Occupy Movement in the U.S. was a reflection of globalization inspired by the Arab Spring and grounded in Ghandi’s model of non-violent protestation. However, it was largely ineffective at significantly shifting public policy. This study was conducted during the heart of the movement, spring 2012, and utilized a qualitative phenomenological design from an international psychology perspective to explore the meaning, perception, change, and motivation of Occupy members at one of the most prominent Occupy Movement locations, Washington, D.C.’s McPherson Square Park. Additionally, the study explored the understanding of, attitudes toward, and willingness to assist the Occupy Movement of students and faculty at a professional psychology school located in one of the buildings overlooking McPherson Square Park. Semi-structured and online interviews of Occupy members (N=10) and psychology school students (N=10) and faculty (N=3) were conducted. An online survey was also utilized for each group, Occupy members (N=8) and students (N=40). The results indicate that Occupy DC members valued diversity of opinion, goals, and viewpoints; however the acceptance and promotion of varying viewpoints appears to have disjointed occupiers’ vision and the professional psychology school’s student and faculty knowledge of the meaning and reason behind Occupy in DC. The first signs of the reasons for the eventual decline of Occupy DC were identified, such as a loss of coherent vision and forced removal from the park for environmental and health reasons. These signs also acted as barriers that kept the neighboring professional psychology students and faculty from providing assistance to the occupiers.